A study on the use of listening test-taking strategies and their relationship with students' performance at Que Vo I Upper Secondary School in Bacninh = Nghiên cứu việc sử dụng các thủ thuật nghe trong các bài kiểm tra nghe của học sinh và mối quan hệ của - Lê, Thị Thúy Hà (ĐHNN, 2017)
44 p. + CD-ROM